# Find the closed form value for this sum: `sum_(i = 1)^n (i^2 + 2*i)`

*print*Print*list*Cite

### 1 Answer

The value of `sum_(i=1)^n (i^2 + 2*i)` = `sum_(i = i)^n ( i^2) + sum_(i = 1)^n 2*i`

The sum of the squares of the first n natural numbers is given `n^3/3 + n^2/2 + n/6` and the sum of the first n natural numbers is `n^2/2 + n/2`

`sum_(i = 1)^n i^2 + sum_(i = 1)^n 2*i`

=> `n^3/3 + n^2/2 + n/6 + n^2/2 + n/2`

=> `n^3/3 + n^2 + (2n)/3`

**The required value of the sum is** `n^3/3 + n^2 + (2n)/3`